The Neuromodulator-Encoding sadA Gene Is Widely Distributed in the Human Skin Microbiome - Luqman, Arif; Zabel, Susanne; Rahmdel, Samane; Merz, Britta; Gruenheit, Nicole; Harter, Johannes; Nieselt, Kay; Götz, Friedrich (Frontiers in Microbiology, 2020)
Trace amines (TA) are endogenously produced in mammals, have a low concentration in the central nervous system (CNS), but trigger a variety of neurological effects and intervene in host cell communication. It emerged that neurotransmitters and TA are produced also by the microbiota. As it has been shown that TA contribute to wound healing, we examined the skin microbiome of probands using shotgun metagenomics. The phyla Actinobacteria, Proteobacteria, Firmicutes, and Bacteroidetes were predominant. Since SadA is a highly promiscuous TA-producing decarboxylase in Firmicutes, the skin microbiome was specifically examined for the presence of sadA-homologous genes. By mapping the reads of certain genes, we found that, although there were less reads mapping to sadA than to ubiquitous housekeeping genes (arcC and mutS), normalized reads counts were still >1000 times higher than those of rare control genes (icaA, icaB and epiA). At protein sequence level SadA homologs were found in at least 7 phyla: Firmicutes, Actinobacteria, Proteobacteria, Bacteroidetes, Acidobacteria, Chloroflexi, and Cyanobacteria, and in 23 genera of the phylum Firmicutes. A high proportion of the genera that have a SadA homolog belong to the classical skin and intestinal microbiota. The distribution of sadA in so many different phyla illustrates the importance of horizontal gene transfer (HGT). We show that the sadA gene is widely distributed in the human skin microbiome. When comparing the sadA readcounts in the probands, there was no correlation between age and gender, but an enormous difference in the sadA readcounts in the microbiome of the individuals. Since sadA is involved in TA synthesis, it is likely that the TA content of the skin is correlated with the amount of TA producing bacteria in the microbiome. In this way, the microbiome-generated TA could influence signal transmission in the epithelial and nervous system.